'Night, mother a play - Norman, Marsha 1947- (Hill and Wang, 1983)
Told in just 90 minutes, the devastating play writes about a young woman who "looks out at the world and sees : NOT FAIR."
Keywords: Mother and child -- Drama; Suicide -- Drama; One-act plays